PARTISIPASI SETENGAH HATI DALAM PELAKSANAAN GOOD GOVERNANCE PADA PEMERINTAH DESA - Zakiyah, Ummi; idrus, iqbal aidar (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2018)
The foundation of the principle of Good Governance in the village government is the ideal that all parties want to achieve. In practice, realizing good governance at the village level still has many challenges, one of which is related to the participation of people whose levels are still low, so that serious efforts are needed to create good governance. This paper will explain the level of village community participation in every activity and program carried out by the village government that leads to good government. The research method used in the study was descriptive qualitative. The form of public participation is still limited to ceremonial participation, which means that new communities participate when there are activities in terms of competition, social service, or commemoration of holidays. Community participation has not touched substantive land such as decision making.